2005
DOI: 10.1124/jpet.105.089284
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ca2+Channels by Opioid Receptor-Like 1 Receptors Natively Expressed in Rat Stellate Ganglion Neurons Innervating Cardiac Muscle

Abstract: Postganglionic sympathetic nerve terminals innervate cardiac muscle and express opioid receptor-like 1 (ORL1) receptors, the most recently described member of the opioid receptor subclass. ORL1 receptors are stimulated by the endogenous heptadecapeptide nociceptin (Noc). To better understand how the signaling events by Noc regulate sympathetic neuron excitability, the goal of the present study was to determine whether sympathetic stellate ganglion (SG) neurons, innervating the heart, natively express ORL1 opio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
0
17
0
4
Order By: Relevance
“…Morphine also acts at m-opioid receptors that are expressed in the CNS (Diaz et al, 1995;Goodchild et al, 2004), where a clear correlation between physiologic effects and modulation of Ca V 2.2 channels is more difficult to establish. Although morphine is considered selective for m-opioid receptors, selective agonists of the other three members of the extended opioid receptor family (i.e., d-and k-opioid receptors, and nociceptin receptors) also functionally inhibit Ca V 2.2 channels (Gross and Macdonald, 1987;Moises et al, 1994;Motin et al, 1995;Morikawa et al, 1998;Toselli et al, 1999;Larsson et al, 2000;Yeon et al, 2004;Ruiz-Velasco et al, 2005;Evans et al, 2010). As in the case of m-opioid receptors, their activation induces analgesia in various animal models of pain (King et al, 1997;Darland et al, 1998;Field et al, 1999;Mika et al, 2001;Courteix et al, 2004;Nozaki et al, 2012).…”
Section: Ca V 2 Channel Pathophysiologymentioning
confidence: 99%
“…Morphine also acts at m-opioid receptors that are expressed in the CNS (Diaz et al, 1995;Goodchild et al, 2004), where a clear correlation between physiologic effects and modulation of Ca V 2.2 channels is more difficult to establish. Although morphine is considered selective for m-opioid receptors, selective agonists of the other three members of the extended opioid receptor family (i.e., d-and k-opioid receptors, and nociceptin receptors) also functionally inhibit Ca V 2.2 channels (Gross and Macdonald, 1987;Moises et al, 1994;Motin et al, 1995;Morikawa et al, 1998;Toselli et al, 1999;Larsson et al, 2000;Yeon et al, 2004;Ruiz-Velasco et al, 2005;Evans et al, 2010). As in the case of m-opioid receptors, their activation induces analgesia in various animal models of pain (King et al, 1997;Darland et al, 1998;Field et al, 1999;Mika et al, 2001;Courteix et al, 2004;Nozaki et al, 2012).…”
Section: Ca V 2 Channel Pathophysiologymentioning
confidence: 99%
“…NOP receptor inhibition of N-type calcium conductance is likely mediated by binding of the dissociated Gbg subunit directly to the channel. This binding event is thought to reduce voltage activation of channel pore opening Snutch, 1998, 2002;Beedle et al, 2004;Yeon et al, 2004;Ruiz-Velasco et al, 2005). Furthermore, it has also been recently reported that NOP receptors use Rho-associated coiled-coil-containing protein kinase (ROCK) and LIM domain kinase (LIMK) in the regulation of voltage-dependent Ca 2+ channels (Mittal et al, 2013).…”
Section: Signal Transduction Pathways Activated By Nop Receptor mentioning
confidence: 99%
“…1A (right). This protocol has been used routinely to study the agonist-mediated voltage-dependent inhibition of Ca 2ϩ channel currents, including N/OFQ (Ruiz-Velasco et al, 2005). The protocol consists of a test pulse to ϩ10 mV (prepulse, F) followed by a large depolarizing conditioning test pulse to ϩ80 mV, a brief return to Ϫ80 mV, and followed by a test pulse to ϩ10 mV (postpulse, E).…”
Section: Sg Neuron Isolationmentioning
confidence: 99%
“…The plasmid coding for rat NOP receptor was subcloned in pCI and injected at a final concentration of 100 to 800 ng/l. We isolated and cloned this receptor construct previously from SG neurons and found that adult rats express a single NOP receptor subtype or one splice variant (Ruiz-Velasco et al, 2005). The plasmid coding for the human opioid peptide (MOP) receptor was subcloned in pcDNA3.1 (Invitrogen) and injected at a concentration of 500 ng/l.…”
Section: Sg Neuron Isolationmentioning
confidence: 99%
See 1 more Smart Citation